Determinants of Dengue Fever Incidence in Dense Residential Areas: A Systematic Literature Review - Nurdin; Martini Martini; Mursid Rahardjo (Majalah Kesehatan Indonesia, 2023)
The problem of dengue hemorrhagic fever (DHF) has become a major concern for the government in addition to other diseases both infectious and non-communicable. DHF every year always brings victims and is difficult to avoid. This study aims to determine the determinants of dengue incidence. This research uses the literature review method from various reference sources such as scientific journals, manuals from ministries/institutions, proceedings, books, and others. The results of this research reported that there are four determinants that affect the incidence of dengue fever in Indonesia, namely social, economic, environmental, and institutional factors. In the social factor, there are 4 sub-factors, while in the economic factor there are four, in the environment, there are seven and 11 of the institutional sub-factors. This research recommends that in overcoming dengue fever, it is necessary to do it thoroughly, involve all interested actors and be carried out programmatically and sustainably.